2006
DOI: 10.1242/dev.02351
|View full text |Cite
|
Sign up to set email alerts
|

The level of sonic hedgehog signaling regulates the complexity of cerebellar foliation

Abstract: Foliation of the mouse cerebellum occurs primarily during the first 2 weeks after birth and is accompanied by tremendous proliferation of granule cell precursors (GCPs). We have previously shown that sonic hedgehog (Shh) signaling correlates spatially and temporally with fissure formation, and that Gli2 is the main activator driving Shh induced proliferation of embryonic GCPs. Here, we have tested whether the level of Shh signaling regulates the extent of cerebellar foliation. By progressively lowering signali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
294
3
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 269 publications
(315 citation statements)
references
References 47 publications
12
294
3
2
Order By: Relevance
“…Interestingly, they both show different expression patterns along the anterior-posterior axis in the EGL or in Purkinje cells. Unlike COUP-TFI, COUP-TFII is highly expressed only in the anterior half of the cerebellum in a manner similar to that of Sonic hedgehog (Shh), which is important for cerebellar foliation (Corrales et al, 2004(Corrales et al, , 2006. Since COUP-TFII is more likely to be a downstream target of Shh signaling (Krishnan et al, 1997;Takamoto et al, 2005), it is reasonable to expect that COUP-TFII may play an important role in cerebellar development.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, they both show different expression patterns along the anterior-posterior axis in the EGL or in Purkinje cells. Unlike COUP-TFI, COUP-TFII is highly expressed only in the anterior half of the cerebellum in a manner similar to that of Sonic hedgehog (Shh), which is important for cerebellar foliation (Corrales et al, 2004(Corrales et al, , 2006. Since COUP-TFII is more likely to be a downstream target of Shh signaling (Krishnan et al, 1997;Takamoto et al, 2005), it is reasonable to expect that COUP-TFII may play an important role in cerebellar development.…”
Section: Resultsmentioning
confidence: 99%
“…The Purkinje neurons represent a further, important component of the anchoring centers. It has been recently shown (Corrales et al, 2004(Corrales et al, , 2006 that Shh secreted by Purkinje cells regulates the number of folia via its influence on granule cell precursor proliferation in the egl. The analysis of Engrailed2 (En2) mutants (Sudarov and Joyner, 2007) suggests the existence of a morphogenetic clock that normally controls the timing of the genetic and cellular events that direct formation of the anchoring centers; the loss of En2 disturbs this morphogenetic clock leading to aberrations in the formation of fissures.…”
Section: Defects Of Cerebellum Fissuresmentioning
confidence: 99%
“…The molecular mechanisms underlying the spatial and temporal onset of fissure formation (Corrales et al, 2004(Corrales et al, , 2006 are currently under study in genetic mutants: the levels of sonic hedgehog (Shh), a secreted factor expressed in Purkinje cells from prenatal day 17.5 onwards in the mouse, regulate the extent, but not the pattern, of cerebellar foliation. Shh also regulates the number of folia through its influence on granule cell precursor proliferation.…”
mentioning
confidence: 99%
“…278 Among multiple other roles, SHH is important for normal embryonic patterning, including the development of midbrain and hindbrain structures. 279,280 One study has suggested that the administration of SHH can partially attenuate the neurotoxic effects of valproic acid on early serotonergic neuronal development. 252 SHH may produce effects through the PI3K pathway, 281 which is also important for normal brain development.…”
Section: Genes Responsive To Environmental Factorsmentioning
confidence: 99%